The Bremen-Cog: environmental issues - Belasus, Mike; Daly, Aoife; Martins, Adolfo Miguel (Zenodo, 2021)
The Bremen-Cog was dated by dendrochronology in the 1960s when the discipline was in its infancy. The felling date of winter 1378/79 in the Weser Uplands was established and confirmed in 2007. In 2016 a new comprehensive analysis of the ship was made possible. All analysed samples are from trees likely felled in the last quarter of the 14th century in the direct hinterlands of Bremen. Furthermore, an attempt at tree morphology reconstruction and a detailed investigation into the trees’ growing features were carried out, revealing a poor timber quality, which was originally not necessarily intended for the purpose of shipbuilding. : The research presented in this paper is a result of activities within three research projects. Daly and Belasus are currently funded by the project entitled "Northern Europe's timber resource – chronology, origin and exploitation (TIMBER)" (2016‑2021), which has received funding from the European Research Council (ERC) under the European Union's Horizon 2020 research and innovation programme (grant agreement No. 677152). Belasus was previously funded by the project "From the North Sea to the Norwegian Sea – Interdisciplinary research on the Hanse" (2015‑2018), which received financing through the Leibniz Competition 2015, funding line 4: "Promoting women for academic leadership positions" by the Leibniz Foundation, Germany, during which the dendrochronological analysis was generously financed by the support association of the German Maritime Museum (Förderverein Deutsches Schiffahrtsmuseum e.V.). Martins was funded through the project "ForSeaDiscovery", supported by the People Programme (Marie Curie Actions) of the European Union's Seventh Framework Programme (FP72007‑2013) under REA grant agreement no. PITN-GA 2013‑607545. The authors are very grateful to the German Maritime Museum for their generosity in allowing us to examine the Bremen ship.